Cost-utility analysis of using paliperidone palmitate in schizophrenia in China - Luo, Rui; Lu, He; Li, Hengfen (Frontiers in Pharmacology, 2023)
Long-acting injections (LAIs) of paliperidone palmitate have been shown to improve medication adherence and relieve psychotic symptoms. However, the specific cost-utility analysis of these LAIs in schizophrenia in China remains unclear. Methods: A multi-state Markov model was constructed to simulate the economic outcomes of patients with schizophrenia in China who received paliperidone palmitate one-month formulation (PP1M), paliperidone palmitate three-month formulation (PP3M), and paliperidone extended-release (ER). A cost-utility analysis was conducted, mostly derived from published literature and clinical databases. All costs and utilities were discounted at a rate of 5% per annum. The primary outcome measure was the incremental cost-effectiveness ratios (ICERs). A series of sensitivity analyses were also applied. Results: After 20 years, compared to ER, using PP1M resulted in an increased discounted cost from 36,252.59 to 43,207.28. This increased cost was associated with a gain in quality-adjusted life years (QALYs) from 8.60 to 9.45. As a result, the ICER for PP1M was estimated to be 8,247.46/QALY, which was lower than the willingness-to-pay (WTP) threshold of 12,756.55/QALY. When using PP3M instead of ER, the incremental cost was 768.81 and the incremental utility was 0.88 QALYs, projecting an ICER of 873.13/QALY, which was also lower than the WTP threshold of 12,756.55/QALY. The univariate sensitivity analysis showed that the costs of PP1M, PP3M, and ER had the greatest impact on ICERs. The probability sensitivity analysis (PSA) revealed that when the WTP thresholds were 12,756.55/QALY, the probability of PP1M and PP3M being cost-effective was 59.2% and 66%, respectively. Conclusions: From the Chinese healthcare system perspective, PP3M and PP1M are both more cost-effective compared to ER, and PP3M has notable cost-utility advantages over PP1M.